New Zinc(II) Dyes: Photophysical Properties and Enhanced Two-Photon Absorption - Cao, Yuanle; Xu, Dongling; Yang, Mingdi; Wang, Yang; Zhou, Feixia; Zhou, Hongping (Asian Journal of Chemistry, 2013)
A series of zinc(II) complexes (dyes 1-5) based on 4'-(4-[4-(imidazole)styryl]phenyl)-2,2':6',2"-terpyridine have been synthesized and fully characterized. Linear and non-linear optical properties of them were investigated in detail. Experimental results reveal that the maximum two-photon absorption (TPA) cross-section of these five two-photon fluorescence complexes are 646, 367, 180, 456 and 246 GM for dyes 1-5 in DMF, respectively, which are extraordinary larger than that of ligand with the maximum values of 149 GM in the DMF. Besides, with the same metal cation, the two-photon absorption cross-section vary by the order of Cl > SCN > Br > ClO4 > I, which suggests that the two-photon absorption cross-sections of complexes display a large dependence on the choice of anions.